Dasar Keberlakuan Pasal 14 Angka 8 Akta Notaris Terhadap Pendirian Lembaga Bantuan Hukum Berbentuk Yayasan - Rizkawati Gasin; Weny Almoravid Dungga; Zamroni Abdussamad (Deposisi: Jurnal Publikasi Ilmu Hukum, 2024)
This study aims to determine and analyse the basis for the enactment of Article 14 Point 8 of the Notary Deed towards the establishment of the foundation. The research method used in this research is Normative with a Legislation approach (statue approach) and case approach. The results showed that the validity of Article 14 number 8 of the Notarial Deed on the Establishment of a Legal Aid Institution in the Form of a Foundation does not have strong legal force because there are no rules that prohibit the management from concurrently implementing activities as contained in article 14 number 8 of the Notarial Deed on the Establishment of a Legal Aid Institution in the Form of a Foundation.